Professional Applications of Information Literacy: Helping Researchers Learn to Evaluate Journal Quality - Dale, Jenny; Craft, Anna R. (Serials review, 2021)
Evaluating journals can be challenging, especially for new researchers. This article discusses the application of information literacy skills and techniques, such as lateral reading, in the context of teaching researchers to evaluate journal quality and avoid predatory journals. Many libraries focus information literacy efforts on helping students develop skills in reflective discovery, evaluation, and ethical use of information. But information literacy skills are critical for lifelong learning, and similar techniques can be applied to help faculty and other researchers evaluate publication venues. This article will examine the connections between information literacy skills and scholarly communications, and will offer methods and practices for readers who wish to build on these connections in their own work.